Estudo descritivo da circulação sobre a plataforma interna e o efeito ilha : estudo de caso de Guarapari (ES) - Guaitolini, Priscila Barboza (2010)
This study evaluated the circulation in the inner continental shelf along the city of Guarapari (ES) using data collected during the Victory 8B artificial reef monitoring. The goal of this study was to characterize and analyze the hydrodynamics in this region using three sets of ADCP data sets (June 23, 2006, 8 Mar 2007 and 26 October 2007). The current data processing included the exclusion of bad data, removal of the tidal signal using a barotropic tidal modeling information, the use of a running-average filter and trianglebased cubic interpolate onto produce horizontal and vertical maps. The results showed that average current were southwestward with most intense speeds in October 2007 (0.28 m.s-1) followed by March 2007 (0.21 ms-1) and June 2006 (0.19 ms-1). Cross-shore transects showed a two-layer ocean in June and October. The flow was directed offshore close to the surface and onshore in the remaining of the water column. Moreover the currents rotated cyclonically with the increase in depth. These patterns were similar to the upwelling processes along the coast regions. This scheme was not observed in March when the currents were southwestward from top to bottom even though the winds were northeast suggesting that an external force not yet considered in this analysis is driving the system. Regarding the island effect it was observed in all three data sets the presence of a wake caused by the Ilhas Rasas that maybe associated with the release of eddies, in accordance with the Island Parameter P estimated.